Sodium ferric pyrophosphate positive electrode material as well as preparation method and application thereof
The preparation of sodium ferrophosphate phosphate positive electrode material through wet ball milling and ultrasonic dispersion technology has solved the problems of low reversible capacity and poor cycle stability in commercial production of sodium ferrophosphate phosphate electrode material in the prior art, and achieved high efficiency, Environmentally friendly material preparation, suitable for large-scale production.
Patent Information
- Application Number
- CN202411803436.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing sodium ferric pyrophosphate electrode materials have problems such as low reversible capacity, poor cycle stability, serious pollution in the preparation process and difficulty in rapid and large-scale production.
Wet ball milling and ultrasonic dispersion technology are used to mix iron phosphate with graphene oxide, and the positive electrode material of sodium ferric pyrophosphate is prepared by spray drying and sintering to achieve uniform particle size and high conductivity of the material and avoid nitrogen oxide contamination.
The reversible capacity and cycle stability of the sodium ferric pyrophosphate positive electrode material is improved, and the clean and environmentally friendly high-efficiency preparation process is achieved, which is suitable for large-scale commercial production.
Smart Images

Figure CN119284864A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium batteries, and in particular relates to a sodium iron pyrophosphate positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium resources are limited and their prices fluctuate dramatically. As the demand for lithium continues to grow, resource shortages are becoming increasingly prominent. Sodium, as an element with abundant reserves and relatively low prices in the earth's crust, has become a new focus in battery technology research. Compared with lithium, sodium has a lower extraction cost, so sodium-ion batteries are considered to be an effective solution to reduce dependence on lithium. Sodium ferric pyrophosphate, as a positive electrode material for sodium-ion batteries, has a wide range of application potentials and is becoming a research focus.
[0003] Sodium iron pyrophosphate has become the first choice for industrialization of polyanion compound positive electrodes due to its high energy density, high safety performance and low price of raw materials. At present, there are four main methods for preparing sodium iron pyrophosphate electrodes, namely solid phase method, sol-gel method, hydrothermal synthesis method and spray drying method. Among them, the solid phase method adopts the method of directly mixing and reacting solids, which is low in cost but poor in sample uniformity and material performance, and cannot meet commercial requirements. Since the sol-gel method mixes raw materials in the liquid phase, the precursor solution has good chemical uniformity, small particle size, easy to control reaction process, simple equipment, but high energy consumption and serious pollution. For nanocrystals synthesized by hydrothermal synthesis, the particle size distribution is uniform, the grains are fully developed, and the raw materials are relatively cheap, and crystals with ideal chemical ratios can be obtained. However, the synthesis process is complicated and the cost is high. The spray drying technology can quickly dry and solidify liquid particles during the spray drying process, reducing the agglomeration of powder particles. The sintered material has a spherical morphology with uniform morphology. In addition, the spray drying technology can efficiently process large quantities of materials in a short period of time, making it suitable for industrial production and has high application potential in the field of large-scale energy storage materials.
[0004] The commercial synthesis methods of sodium ferric pyrophosphate are mainly hydrothermal and sol-gel methods. The iron source mainly relies on soluble nitrates, and the production efficiency is difficult to meet the requirements of large-scale commercial production. In addition, ferric nitrates are usually controlled drugs. As production raw materials, they will decompose to produce nitrogen oxides during later processing, causing pollution and equipment loss, increasing production costs, and it is difficult to meet actual production requirements, which hinders its commercial production and application.
[0005] At present, the conductivity and electrochemical performance of this material are improved through nano-sizing, doping and other technical means. However, the sodium iron phosphate pyrophosphate obtained by the existing technology still has the defects of low reversible capacity, poor cycle stability, serious pollution in the preparation process and difficulty in rapid and large-scale production. Summary of the invention
[0006] The object of the present invention is to provide a sodium iron phosphate pyrophosphate positive electrode material and a preparation method and application thereof. The sodium iron phosphate pyrophosphate positive electrode material prepared by the method provided by the present invention is applied to sodium batteries, which can further improve the reversible capacity and cycle stability. The preparation process is clean and environmentally friendly, and is suitable for large-scale commercial production.
[0007] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps: The ferric phosphate, sodium dihydrogen phosphate and sodium citrate are mixed and wet ball-milled to obtain a ball-milled material; The ball mill, graphene oxide and water are mixed, and first stirring, ultrasonic dispersion and second stirring are performed in sequence to obtain a mixed slurry; spray drying the mixed slurry to obtain a precursor; The precursor is sintered to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0008] Preferably, the ferric phosphate salt comprises ferric phosphate and / or ferrous phosphate; The molar ratio of the ferric phosphate, sodium dihydrogen phosphate and sodium citrate is 6:13-16:4.
[0009] Preferably, the dispersion medium of the wet ball milling is water, and the volume of the water is 1 / 2 to 2 / 3 of the volume of the ball mill; The diameter of the ball milling beads used in the wet ball milling includes 3 mm, 5 mm, 10 mm or 20 mm; the total volume of the ball milling beads accounts for 1 / 4 of the volume of the ball mill jar.
[0010] Preferably, the wet ball milling condition parameters include: the ball mill speed is 400 rpm, the star disk speed is 4 rpm; the ball mill is set to rotate forward for 10 minutes, rest for 5 minutes, reverse for 10 minutes, and rest for 5 minutes as one cycle, and the cycle is repeated 10 times.
[0011] Preferably, the mass ratio of the graphene oxide to the ball mill is no more than 3%.
[0012] Preferably, the first stirring speed is 300-400 rpm, and the time is 10-20 min; The temperature of the ultrasonic dispersion is lower than 25°C; the power of the ultrasonic dispersion is 720-900W, and the time is 30-60min; The second stirring has a rotation speed of 500-600 rpm and a time of 1-2 h.
[0013] Preferably, the spray drying condition parameters include: inlet temperature of 200-280°C, outlet temperature of above 130°C, and feed rate of 250-400 mL / h.
[0014] Preferably, the sintering temperature is 500-600°C and the holding time is 5-10h; The sintering is carried out in a mixed atmosphere of argon and hydrogen; The volume ratio of argon to hydrogen in the mixed atmosphere is 90-95:10-5.
[0015] The present invention also provides a sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method described in the above technical solution.
[0016] The present invention also provides the use of the sodium iron phosphate pyrophosphate positive electrode material described in the above technical solution in a sodium battery.
[0017] The invention provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps: mixing ferric phosphate, sodium dihydrogen phosphate and sodium citrate, and performing wet ball milling to obtain a ball mill material; mixing the ball mill material, graphene oxide and water, and sequentially performing a first stirring, ultrasonic dispersion and a second stirring to obtain a mixed slurry; spray drying the mixed slurry to obtain a precursor; and sintering the precursor to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0018] The sodium iron phosphate pyrophosphate positive electrode material obtained by the pollution-free, high-efficiency, low-cost preparation method provided by the present invention has uniform particle size, excellent conductivity and high structural stability, and through the two key steps of ball milling and ultrasound, the insoluble iron phosphate raw material is first crushed to micrometer level by ball milling, and then crushed to nanometer level by ultrasound and the material is mixed evenly, so as to solve the problem of insufficient solid phase reaction caused by using iron phosphate as raw material. The material is applied to sodium ion batteries, which solves the nitrogen oxide pollution problem of industrial preparation of sodium iron phosphate pyrophosphate, and can further improve the reversible capacity and cycle stability.
[0019] The purpose of the present invention is to provide a method combining wet ball milling, ultrasonic mixing, spray drying and sintering to overcome the difficulties in the synthesis process of pure phase mixed ionic iron-based phosphate sodium ion positive electrode from laboratory to commercial application, and achieve the goal of zero pollutant emission in the synthesis process. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the preparation method provided by the present invention; Figure 2 This is a scanning electron microscope (SEM) image of the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 3This is an X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 4 This is a scanning electron microscope (SEM) image of the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Figure 5 This is an X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Figure 6 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 7 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 8 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Fig. 9 This is a rate performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Fig.10 This is a constant current charge and discharge curve of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2; Fig.11 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2; Fig.12 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2; Fig.13 This is a rate performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2; Fig.14 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3; Fig.15 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3; Fig.16 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3; Fig.17 This is a rate performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3; Fig.18 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Fig.19 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Fig. 20 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Fig.21 This is a rate performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Fig. 22 This is a constant current charge and discharge curve of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2; Fig.23 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2; Fig.24 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2; Fig.25 This is a rate performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2; Fig.26 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3; Fig. 27 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3; Fig.28 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3; Fig.29 This is a rate performance diagram of a sodium battery assembled with the sodium iron pyrophosphate positive electrode material obtained in Comparative Example 3. DETAILED DESCRIPTION
[0021] The present invention provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, comprising the following steps: The ferric phosphate, sodium dihydrogen phosphate and sodium citrate are mixed and wet ball-milled to obtain a ball-milled material; The ball mill, graphene oxide and water are mixed, and first stirring, ultrasonic dispersion and second stirring are performed in sequence to obtain a mixed slurry; spray drying the mixed slurry to obtain a precursor; The precursor is sintered to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0022] The invention mixes ferric phosphate, sodium dihydrogen phosphate and sodium citrate, and performs wet ball milling to obtain ball milling material.
[0023] In the present invention, the ferric phosphate salt includes ferric phosphate and / or ferrous phosphate; the ferrous phosphate is preferably Fe3(PO4)2·8H2O; the sodium dihydrogen phosphate is preferably NaH2PO2·2H2O; the molar ratio of the ferric phosphate salt, sodium dihydrogen phosphate and sodium citrate is preferably 6:13~16:4.
[0024] In the present invention, the dispersion medium of the wet ball milling is preferably water, and more preferably deionized water; the volume of the water is preferably 1 / 2 to 2 / 3 of the volume of the ball mill; the diameter of the ball milling beads used in the wet ball milling is preferably 3 mm, 5 mm, 10 mm or 20 mm; the volume of the ball milling beads is preferably 1 / 4 of the volume of the ball mill.
[0025] In the present invention, the wet ball milling condition parameters preferably include: the ball mill speed is 400rpm, the star disk speed is 4rpm; the ball mill is set to rotate forward for 10min, rest for 5min, reverse for 10min, and rest for 5min as one cycle, and the cycle is repeated 10 times.
[0026] In the present invention, mixing by wet ball milling can significantly reduce the particle size, effectively grind large particles into smaller particles, and make the size of insoluble iron phosphate reach micrometer level, while ensuring the uniformity of particle size. In addition, ball milling can fully mix different components to ensure uniform distribution of materials, which is particularly suitable for the preparation of composite materials. In addition, ball milling process parameters can be flexibly adjusted according to material requirements, such as time, speed and grinding ball size, etc., to meet the production requirements of different electrode materials.
[0027] After the wet ball milling, the present invention also preferably includes filtering the obtained system, and the sieve aperture used for the filtration is preferably 200 meshes.
[0028] After obtaining the ball mill, the present invention mixes the ball mill, graphene oxide and water, and sequentially performs first stirring, ultrasonic dispersion and second stirring to obtain a mixed slurry.
[0029] In the present invention, the mass ratio of the graphene oxide and the ball mill is preferably not more than 3%. In the present invention, the rotation speed of the first stirring is preferably 300-400 rpm, and the time is preferably 10-20 min; the first stirring method is preferably magnetic stirring. In the present invention, the temperature of the ultrasonic dispersion is preferably less than 25°C; the power of the ultrasonic dispersion is preferably 400-600 W, and the time is preferably 30-60 min. In the present invention, the rotation speed of the second stirring is preferably 500-600 rpm, and the time is preferably 1-2 h. In the present invention, by adding graphene oxide, graphene can be obtained in the subsequent sintering process. Graphene can improve the conductivity of the composite material and provide a fast ion diffusion channel for the material, which helps to accelerate the migration rate of sodium ions in the battery, thereby improving the rate performance of the battery.
[0030] In the present invention, ultrasonic dispersion is adopted, and the cavitation effect generated by ultrasonic waves can refine the material particles, and the insoluble iron phosphate after ball milling can be refined from the micron level to the nanometer level, and it can be evenly dispersed in the medium, effectively avoiding particle aggregation, so that the material reaction is more sufficient; and the material can maintain its uniformity to improve the electrochemical performance of the material.
[0031] After obtaining the mixed slurry, the present invention spray-dries the mixed slurry to obtain a precursor.
[0032] In the present invention, the spray drying condition parameters preferably include: inlet temperature of 200-280°C, outlet temperature of 130°C or above, and feed rate of 250-400 ml / h. In the present invention, during the spray drying process, the mixed slurry is preferably in a stirring state.
[0033] In the present invention, the spray drying technology has the following advantages: (1) Precise control of particle size and morphology: By adjusting the process conditions of spray drying, the size and morphology of the particles can be effectively controlled, making the prepared material more uniform. This uniformity helps to improve the overall performance of the battery. (2) Increase the specific surface area: The spray-dried material has a larger specific surface area, which can increase the contact area between the active material and the electrolyte, thereby improving the efficiency of the electrochemical reaction and the energy output of the battery. (3) Improve the fluidity of the material: Spray drying enables the particles to have good fluidity and compactibility, which is conducive to uniform distribution during electrode manufacturing, reduces defects in production, and improves the consistency and durability of the battery. (4) Reduce particle agglomeration: During the spray drying process, the particles are quickly dried and solidified, reducing the agglomeration of powder particles. This independent particle morphology helps to improve the electrochemical stability of the material and the cycle life of the battery. (5) Ensure the uniformity and purity of the ingredients: Spray drying can make the ingredients evenly mixed during the preparation process, reduce the introduction of impurities, thereby improving the purity and consistency of the material, which is conducive to the optimization of battery performance. (6) Spray drying has the characteristics of rapid drying of materials in a short time, with high drying efficiency, which is conducive to large-scale industrial production.
[0034] After obtaining the precursor, the present invention sintered the precursor to obtain the sodium iron phosphate pyrophosphate positive electrode material.
[0035] In the present invention, the sintering temperature is preferably 500-600°C, and the heating rate to the sintering temperature is preferably 2°C / min; the holding time is preferably 5-10h; the sintering is preferably carried out in a mixed atmosphere of argon and hydrogen; the volume ratio of argon and hydrogen in the mixed atmosphere is preferably 90-95:10-5.
[0036] The schematic flow diagram of the preparation method provided by the present invention is as follows Figure 1 shown.
[0037] The present invention also provides a sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method described in the above technical solution.
[0038] The present invention also provides the use of the sodium iron phosphate pyrophosphate positive electrode material described in the above technical solution in a sodium battery.
[0039] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.
[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1 Fe3(PO4)2·8H2O (10.032 g, 0.020 mol), NaH2PO2·2H2O (7.8005 g, 0.050 mol) and C6H5Na3O7 (3.4409 g, 0.013 mol) were added into a high-energy ball mill, and 35 g of 3 mm diameter ball milling beads, 30 g of 5 mm diameter ball milling beads, 20 10 mm diameter ball milling beads (the volume occupies 1 / 4 of the ball milling jar) and 120 mL of deionized water were added. After sealing, the ball mill speed was set to 400 rpm, the star disk speed was set to 4 rpm, and the ball mill was set to rotate forward for 10 min, rest for 5 min, reverse for 10 min, and rest for 5 min as one cycle, and the cycle was repeated 10 times. After ball milling, the mixed solution was filtered out using a 200-mesh filter, and 200 mL of deionized water was added to dilute it, 0.8 g of graphene oxide was added, and a polypropylene magnet was added. The mixture was stirred at 400 rpm on a stirring table for 10 min, and the magnet was removed. The beaker was then placed in an ultrasonic cell crusher, and the beaker was placed in a cooling circulation cup. The mixture was ultrasonically treated for 1 h, and the ultrasonic power was 500 W. The temperature was controlled below 25 ° C. After that, the magnet was added, and the mixture was stirred at 500 rpm on a stirring table for 1 h. The solution after stirring was placed on a stirring table. During the spray drying process, the solution was ensured to be in a stirring state. The solution was dried using a spray dryer at a feed rate of 300 mL / h, a spray inlet temperature of 270° C., and an outlet temperature of 130° C. to obtain a precursor. The obtained precursor was placed in a quartz boat and placed in a tube furnace. The volume of argon and hydrogen was 95:5, the sintering temperature was 500°C, the heating rate was 2°C / min, and the insulation time was 5h to obtain sodium iron pyrophosphate positive electrode material.
[0042] Example 2 Fe3(PO4)2·8H2O (10.032 g, 0.020 mol), NaH2PO2·2H2O (7.6445 g, 0.049 mol) and C6H5Na3O7 (3.4409 g, 0.013 mol) were added into a high-energy ball mill, and 35 g of 3 mm diameter ball milling beads, 30 g of 5 mm diameter ball milling beads, 20 10 mm diameter ball milling beads (the volume occupies 1 / 4 of the ball milling jar) and 120 mL of deionized water were added. After sealing, the ball mill speed was set to 400 rpm, the star disk speed was set to 4 rpm, and the ball mill was set to rotate forward for 10 min, rest for 5 min, reverse for 10 min, and rest for 5 min as one cycle, and the cycle was repeated 10 times. After ball milling, the mixed solution was filtered out using a 200-mesh filter, and 200 mL of deionized water was added to dilute it, 0.8 g of graphene oxide was added, and a polypropylene magnet was added. The mixture was stirred at 400 rpm on a stirring table for 10 min, and the magnet was removed. The beaker was then placed in an ultrasonic cell crusher, and the beaker was placed in a cooling circulation cup. The mixture was ultrasonically treated for 1 h, and the ultrasonic power was 500 W. The temperature was controlled below 25 ° C. After that, the magnet was added, and the mixture was stirred at 500 rpm on a stirring table for 1 h. The solution after stirring was placed on a stirring table. During the spray drying process, the solution was ensured to be in a stirring state. The solution was dried using a spray dryer at a feed rate of 300 mL / h, a spray inlet temperature of 270° C., and an outlet temperature of 130° C. to obtain a precursor. The obtained precursor was placed in a quartz boat and placed in a tube furnace. The volume of argon and hydrogen was 95:5, the sintering temperature was 500°C, the heating rate was 2°C / min, and the insulation time was 5h to obtain sodium iron pyrophosphate positive electrode material.
[0043] Example 3 Fe3(PO4)2·8H2O (10.032 g, 0.020 mol), NaH2PO2·2H2O (7.9565 g, 0.051 mol) and C6H5Na3O7 (3.4409 g, 0.013 mol) were added into a high-energy ball mill, and 35 g of 3 mm diameter ball milling beads, 30 g of 5 mm diameter ball milling beads, 20 10 mm diameter ball milling beads (the volume occupies 1 / 4 of the ball milling jar) and 120 mL of deionized water were added. After sealing, the ball mill speed was set to 400 rpm, the star disk speed was set to 4 rpm, and the ball mill was set to rotate forward for 10 min, rest for 5 min, reverse for 10 min, and rest for 5 min as one cycle, and the cycle was repeated 10 times; After ball milling, the mixed solution was filtered out using a 200-mesh filter, and 200 mL of deionized water was added to dilute it, 0.8 g of graphene oxide was added, and a polypropylene magnet was added. The mixture was stirred at 400 rpm on a stirring table for 10 min, and the magnet was removed. The beaker was then placed in an ultrasonic cell crusher, and the beaker was placed in a cooling circulation cup. The mixture was ultrasonically treated for 1 h, and the ultrasonic power was 500 W. The temperature was controlled below 25 ° C. After that, the magnet was added, and the mixture was stirred at 500 rpm on a stirring table for 1 h. The solution after stirring was placed on a stirring table. During the spray drying process, the solution was ensured to be in a stirring state. The solution was dried using a spray dryer at a feed rate of 300 mL / h, a spray inlet temperature of 270° C., and an outlet temperature of 130° C. to obtain a precursor. The obtained precursor was placed in a quartz boat and placed in a tube furnace. The volume of argon and hydrogen was 95:5, the sintering temperature was 500°C, the heating rate was 2°C / min, and the insulation time was 5h to obtain sodium iron pyrophosphate positive electrode material.
[0044] Comparative Example 1 Fe3(PO4)2·8H2O (10.032 g, 0.020 mol), NaH2PO2·2H2O (7.8005 g, 0.050 mol) and C6H5Na3O7 (3.4409 g, 0.013 mol) were added into a high-energy ball mill, and 35 g of 3 mm diameter ball milling beads, 30 g of 5 mm diameter ball milling beads, 20 10 mm diameter ball milling beads (the volume occupies 1 / 4 of the ball milling jar) and 120 mL of deionized water were added. After sealing, the ball mill speed was set to 400 rpm, the star disk speed was set to 4 rpm, and the ball mill was set to rotate forward for 10 min, rest for 5 min, reverse for 10 min, and rest for 5 min as one cycle, and the cycle was repeated 10 times. After ball milling, the mixed solution was filtered out using a 200-mesh filter, and 200 mL of deionized water was added to dilute it, 0.8 g of graphene oxide was added, and a polypropylene magnet was added. The mixture was stirred at 400 rpm on a stirring table for 10 min, and the magnet was removed. The beaker was then placed in an ultrasonic cell crusher, and the beaker was placed in a cooling circulation cup. The mixture was ultrasonically treated for 1 h, and the ultrasonic power was 500 W. The temperature was controlled below 25 ° C. After that, the magnet was added, and the mixture was stirred at 500 rpm on a stirring table for 1 h. The solution after stirring was placed on a heated stirring table and dried at 80°C for 6 hours to make the solution gel-like, and then placed in a forced air drying oven at 120°C for 12 hours to remove the crystal water to obtain a precursor; The obtained precursor was placed in a quartz boat and placed in a tube furnace. The volume of argon and hydrogen was 95:5, the sintering temperature was 500°C, the heating rate was 2°C / min, and the insulation time was 5h to obtain sodium iron pyrophosphate positive electrode material.
[0045] Comparative Example 2 The sodium iron phosphate pyrophosphate positive electrode material was prepared in the manner of Example 1, except that no graphene oxide was added.
[0046] Comparative Example 3 Sodium iron phosphate pyrophosphate positive electrode material was prepared in the manner of Example 1, except that wet ball milling was not performed, specifically: Fe3(PO4)2·8H2O (10.032 g, 0.020 mol), NaH2PO2·2H2O (7.8005 g, 0.050 mol) and C6H5Na3O7 (3.4409 g, 0.013 mol) were added to a beaker, 120 mL of deionized water was added and stirred for 1 hour, 200 ml of deionized water was added in sequence for dilution, 0.8 g of graphene oxide was added, a polypropylene magnet was added, and the mixture was stirred at 400 rpm on a stirring table for 10 min, the magnet was removed, and the beaker was placed in an ultrasonic cell crusher, and the beaker was placed in a cooling circulation cup, and ultrasonic treatment was performed for 1 hour, the ultrasonic power was 500 W, and the temperature was controlled below 25°C, and then the magnet was added, and the mixture was stirred at 500 rpm on a stirring table for 1 hour; The solution after stirring was placed on a stirring table. During the spray drying process, the solution was ensured to be in a stirring state. The solution was dried using a spray dryer at a feed rate of 300 mL / h, a spray inlet temperature of 270° C., and an outlet temperature of 130° C. to obtain a precursor. The obtained precursor was placed in a quartz boat and placed in a tube furnace. The volume of argon and hydrogen was 95:5, the sintering temperature was 500°C, the heating rate was 2°C / min, and the insulation time was 5h to obtain sodium iron pyrophosphate positive electrode material.
[0047] Performance Testing Test Example 1 Figure 2 This is a scanning electron microscope (SEM) image of the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 3 is the X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1; Figure 2~3 It can be seen that uniform nano-spherical sodium iron phosphate pyrophosphate material was successfully prepared, and the sintered material had correct crystal phase and high purity.
[0048] Figure 4 This is a scanning electron microscope (SEM) image of the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Figure 5is the X-ray diffraction (XRD) diagram of the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1; Figures 4 and 5 It can be seen that the prepared sodium iron phosphate pyrophosphate material is uneven in shape and has a lower purity than that of Example 1.
[0049] Test Example 2 The electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode materials obtained in the test examples and comparative examples; Sodium iron phosphate pyrophosphate cathode material was used as the active material, acetylene black as the conductive agent, and polyvinylidene fluoride (PVDF) as the binder, which were mixed and dissolved in N-methylpyrrolidone (NMP) in a mass ratio of 7:2:1. Stir for 2 hours to form a slurry, which was evenly coated on a battery-grade aluminum foil with a coating thickness of about 120 microns. After the slurry was dried, it was vacuum treated at 80°C for 12 hours. After drying, the material was cut and assembled into a CR2032 button cell in an argon environment. The electrolyte was 1 mol / L NaClO4, the solvent was a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of 1:1, containing 5% fluoroethylene carbonate, the diaphragm was Whatman GF / D glass fiber filter paper, and the sodium foil was used as the counter electrode; Figure 6 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1 is shown in FIG. Figure 6 It can be seen that the coulombic efficiency of the first cycle is 105.9%, the discharge capacity of the 10th cycle is 101.0 mAh / g, and the coulombic efficiency is 100.37%; Figure 7 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1. Figure 7 It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 101mAh / g, and the capacity retention rate is 98.53%; Figure 8 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1. Figure 8 It can be seen that under the high current test (10C), after 100 cycles, the discharge specific capacity is 92.8mAh / g and the capacity retention rate is 100.54%; Fig. 9 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 1 is shown in FIG. Fig. 9It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C. It can be seen that the discharge specific capacities at different current densities are 101.7, 102.5, 98.5, 94.4, 90.8, 86.1, and 79.6 mAh / g, respectively, and the capacity retention rates are 97.8%, 98.5%, 94.7%, 90.7%, 87.3%, 82.8%, and 76.5%, respectively; Fig.10 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2 is shown in FIG. Fig.10 It can be seen that the coulombic efficiency of the first cycle is 110.73%, the discharge capacity of the 10th cycle is 90.4 mAh / g, and the coulombic efficiency is 100.54%; Fig.11 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2. Fig.11 It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 88.7mAh / g, and the capacity retention rate is 98.55%; Fig.12 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2. Fig.12 It can be seen that under the high current test (10C), after 100 cycles, the discharge specific capacity is 80.1mAh / g and the capacity retention rate is 100.37%; Fig.13 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 2 is shown in FIG. Fig.13 It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C. It can be seen that the discharge specific capacities at different current densities are 90.0, 88.2, 85.2, 81.8, 79.8, 76.7, and 74.9 mAh / g, respectively, and the capacity retention rates are 98.5%, 96.6%, 93.3%, 89.5%, 87.4%, 84.0%, and 82.0%, respectively; Fig.14 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3 is shown in FIG. Fig.14 It can be seen that the first cycle coulombic efficiency is 129.53%, the 10th cycle discharge capacity is 86.7mAh / g, and the coulombic efficiency is 100.57%; Fig.15 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3. Fig.15It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 84.7mAh / g, and the capacity retention rate is 100.47%; Fig.16 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3. Fig.16 It can be seen that under the high current test (10C), after 100 cycles, the discharge specific capacity is 77.1mAh / g and the capacity retention rate is 99.48%; Fig.17 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Example 3 is shown in FIG. Fig.17 It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C. It can be seen that the discharge specific capacities at different current densities are 86.4, 83.4, 80.6, 77.0, 72.8, 66.4, and 55.2 mAh / g, respectively, and the capacity retention rates are 99.2%, 95.7%, 92.5%, 88.4%, 83.6%, 76.2%, and 63.4%, respectively; Fig.18 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1 is shown in FIG. Fig.18 It can be seen that the first cycle Coulombic efficiency is 82.6%, the 10th cycle discharge specific capacity is 77.9 mAh / g, and the Coulombic efficiency is 100.62%; Fig.19 This is a low current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1. Fig.19 It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 49.2mAh / g, and the capacity retention rate is 96.3%; Fig. 20 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1. Fig. 20 It can be seen that under the high current test (10C), after 100 cycles, the discharge specific capacity is 47.2mAh / g and the capacity retention rate is 97.1%; Fig.21 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 1 is shown in FIG. Fig.21It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C. It can be seen that the discharge specific capacities at different current densities are 77.9, 72.1, 68.1, 62.4, 57, 52.2, and 41.7 mAh / g, respectively, and the capacity retention rates are 100.5%, 93.0%, 87.9%, 80.5%, 73.5%, 67.4, and 53.8%, respectively; Fig. 22 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2 is shown in FIG. Fig. 22 It can be seen that the first cycle Coulombic efficiency is 109.8%, the 10th cycle discharge capacity is 64mAh / g, and the Coulombic efficiency is 101.9%; Fig.23 This is a low current cycle performance diagram of a sodium battery assembled with sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2. Fig.23 It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 48mAh / g, and the capacity retention rate is 77.9%; Fig.24 This is a high current cycle performance diagram of a sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2. Fig.24 Yes, under high current test (10C), after 100 cycles, the discharge capacity is 31.9mAh / g and the capacity retention rate is 87.6%; Fig.25 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 2 is shown in FIG. Fig.25 It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C. It can be seen that the discharge specific capacities at different current densities are 64, 59.7, 54.4, 47.2, 42.2, 36.1, and 29.2 mAh / g, respectively, and the capacity retention rates are 93.4%, 87.2%, 79.4%, 68.9%, 61.6%, 52.7%, and 42.6%, respectively; Fig.26 The constant current charge and discharge curve of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3 is shown in FIG. Fig.26 It can be seen that the first cycle Coulomb efficiency is 135.45%, the 10th cycle discharge capacity is 61.5 mAh / g, and the Coulomb efficiency is 100.9%; Fig. 27 This is a low current cycle performance diagram of a sodium battery assembled with sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3. Fig. 27It can be seen that under the low current test (1C=129mAh / g), after 100 cycles, the discharge specific capacity is 57.7mAh / g, and the capacity retention rate is 103%; Fig.28 This is a high current cycle performance diagram of a sodium battery assembled with sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3. Fig.28 It can be seen that under the high current test (10C), after 100 cycles, the discharge specific capacity is 38mAh / g, and the capacity retention rate is 100%; Fig.29 The rate performance diagram of the sodium battery assembled with the sodium iron phosphate pyrophosphate positive electrode material obtained in Comparative Example 3 is shown in FIG. Fig.29 It can be seen that in the rate performance test, 10 cycles were tested at current densities of 0.5C, 1C, 2C, 5C, 10C, 20C, and 50C respectively. It can be seen that the discharge specific capacity at different current densities is 61.5, 59.4, 57, 52.6, 48.9, 45.3 and 38.9 mAh / g respectively, and the capacity retention rates are 100.9%, 97.5%, 93.6%, 86.4%, 82.3%, 74.4% and 63.9% respectively.
[0050] The material prepared in Example 1 has a discharge capacity of 101 mAh / g under a low current test (1C = 129 mAh / g), and a capacity retention rate of 98.53% after 100 cycles; under a high current test (10C), after 100 cycles, the discharge capacity is 92.8 mAh / g, and the capacity retention rate is 100.54%; the material prepared in Example 2 has a discharge capacity of 89.7 mAh / g under a low current test (1C = 129 mAh / g), and a capacity retention rate of 98.53% after 100 cycles. 98.55%; under the large current test (10C), after 100 cycles, the discharge capacity is 80.1mAh / g, and the capacity retention rate is 100.37%; the material prepared in Example 3 has a discharge capacity of 84.3mAh / g under the small current test (1C=129mAh / g), and the capacity retention rate is 100.47% after 100 cycles; under the large current test (10C), after 100 cycles, the discharge capacity is 77.1mAh / g, and the capacity retention rate is 99.48%. In the rate performance test, the material of the embodiment performs excellently, and compared with Comparative Examples 1, 2, and 3, it is fully proved that the steps of wet ball milling, ultrasonic mixing and spray drying in this preparation method make the reaction in the material preparation process more sufficient, thereby improving the material performance, and by adding graphene, the conductivity can be improved, which can significantly improve the material rate performance. This preparation method can further improve the reversible capacity and cycle stability, and the preparation process is clean and environmentally friendly, suitable for large-scale commercial production.
[0051] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The following steps are involved: The ferric phosphate, sodium dihydrogen phosphate and sodium citrate are mixed and wet ball-milled to obtain a ball-milled material; The ball mill, graphene oxide and water are mixed, and first stirring, ultrasonic dispersion and second stirring are performed in sequence to obtain a mixed slurry; spray drying the mixed slurry to obtain a precursor; The precursor is sintered to obtain the sodium iron phosphate pyrophosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that: The iron phosphate salt includes ferric phosphate and / or ferrous phosphate; The molar ratio of the ferric phosphate, sodium dihydrogen phosphate and sodium citrate is 6:13-16:
4.
3. The preparation method according to claim 1, characterized in that: The dispersion medium of the wet ball milling is water, and the volume of the water is 1 / 2 to 2 / 3 of the volume of the ball mill; The diameter of the ball milling beads used in the wet ball milling includes 3 mm, 5 mm, 10 mm or 20 mm; the total volume of the ball milling beads accounts for 1 / 4 of the volume of the ball mill jar.
4. The preparation method according to claim 1, characterized in that: The condition parameters of the wet ball milling include: the ball milling speed is 400 rpm, the star disk speed is 4 rpm; the ball milling is set to rotate forward for 10 minutes, rest for 5 minutes, reverse for 10 minutes, and rest for 5 minutes as one cycle, and the cycle is repeated 10 times.
5. The preparation method according to claim 1, characterized in that: The mass ratio of the graphene oxide to the ball mill is no more than 3%.
6. The preparation method according to claim 1, characterized in that: The first stirring speed is 300-400 rpm, and the time is 10-20 min; The temperature of the ultrasonic dispersion is lower than 25°C; the power of the ultrasonic dispersion is 720-900W, and the time is 30-60min; The second stirring has a rotation speed of 500-600 rpm and a time of 1-2 h.
7. The preparation method according to claim 1, characterized in that: The spray drying condition parameters include: inlet temperature of 200-280° C., outlet temperature of above 130° C., and feed rate of 250-400 mL / h.
8. The preparation method according to claim 1, characterized in that: The sintering temperature is 500-600°C and the holding time is 5-10h; The sintering is carried out in a mixed atmosphere of argon and hydrogen; The volume ratio of argon to hydrogen in the mixed atmosphere is 90-95:10-5.
9. The sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the sodium iron phosphate pyrophosphate positive electrode material according to claim 9 in sodium batteries.
Citation Information
Patent Citations
Preparation method and application of sodium-ion battery positive electrode material ferric sodium pyrophosphate
CN114538403A
Preparation method of composite phosphoric acid and ferric sodium pyrophosphate polyanionic positive electrode material and application of composite phosphoric acid and ferric sodium pyrophosphate polyanionic positive electrode material in sodium-ion battery
CN116002650A
Carbon composite phosphoric acid and sodium ferric pyrophosphate material as well as preparation method and application thereof
CN118289725A
Sodium ferric phosphate pyrophosphate / carbon composite positive electrode material as well as preparation method and application thereof
CN118666260A
Cited By
Preparation method and application of carbon-coated boron-silicon dianion-doped ferric sodium pyrophosphate positive electrode material based on spray drying
CN121573688A